FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELAJAR ILMU PENGETAHUAN SOSIAL - Dapriansyah Dapriansyah; R. Gunawan Sudarmanto; Eddy Purnomo (Faculty of Teacher Training and Education, University of Lampung, 2013)
The research used quantitative approach. To collecting the data used questionnaire and documentation. To evaluate the hypothesis, the research used simple regression analysis and multiple regression analysis. Population of research learners about 130 learners by sampling random technique and sample 97 learners. The result of research there is positive influence and learner perception about teaching method of teacher through social science study ambition significantly, positive influence and school condition through social science study ambition significantly, positive influence and emotional management through social science study ambition significantly, positive influence and study ways through social science study ambition significantly, positive influence and learners perception about teaching method of teacher, school condition, emotional management, and study ways together through social science study ambition.Penelitian menggunakan pendekatan kuantitatif dengan teknik pengumpulan data menggunakan angket dan dokumentasi. Untuk menguji hipotesis penelitian dengan menggunakan analisis regresi sederhana dan analisis regresi berganda. Populasi penelitian ini adalah peserta didik sejumlah 130 dengan jumlah sampel 97 peserta. Hasil penelitian terdapat pengaruh positif dan signifikan persepsi peserta didik tentang metode mengajar guru terhadap minat belajar IPS, terdapat pengaruh positif dan signifikan iklim sekolah terhadap minat belajar IPS, terdapat pengaruh positif dan signifikan pengelolaan emosi terhadap minat belajar IPS, terdapat pengaruh positif dan signifikan cara belajar terhadap minat belajar IPS, terdapat pengaruh positif dan signifikan persepsi peserta didik tentang metode mengajar guru, iklim sekolah, pengelolaan emosi dan cara belajar secara bersama-sama terhadap minat belajar IPS.Kata kunci: persepsi peserta didik, iklim sekolah, pengelolaan emosi, cara belajar, minat belajar IPS